Dinamika Islamisme dan Kebijakan Luar Negeri Turki Pada Masa Recep Tayyip Erdogan - Novi Rizka Amalia; Alhakim Fathan Fauzan; Naufaldi Ahmad; Aziz Akmal; Huzaeny Roziqk Heally (The Indonesian Islamic Studies and International Relations Association (Insiera), 2023)
This research discusses the dynamics of Erdogan's leadership in the development of Islamism in Turkey during his leadership, including his influence on foreign policy. This research also discusses from a foreign policy perspective according to Graham T. Allison and makes Erdogan a rational actor in Turkish foreign policy. This research uses a descriptive qualitative method based on literature review and uses a foreign policy perspective. The data presented in this study are literature on foreign policy and also Islamic political identity. The purpose of this research is to find out the dynamics of Islamism during Erdogan's leadership and to find out the direction of his foreign policy. The Rational Actor Model influences the Turkish Identity Political Orientation which is more inclined to Islamic Politics. This foreign policy orientation will also affect Turkey's cooperation with potential countries around it.